New Genera and Species of Ethiopian, Oriental and Neotropical Reduviidae (Hemiptera - Heteroptera). - Miller, Norman Cecil Egerton (Contributions to Entomology = Beiträge zur Entomologie, 1956)
Nomenclatural Actsamoena Miller, 1956 (Anapothea), spec. n.nana Miller, 1956 (Glymmatophora), spec. n.longiceps Miller, 1956 (Haematoloecha), spec. n.asper Miller, 1956 (Oncocephalus), spec. n.breddini Miller, 1956 (Oncocephalus), spec. n.dubius Miller, 1956 (Oncocephalus), spec. n.paganus Miller, 1956 (Oncocephalus), spec. n.sanguiniventris Miller, 1956 (Pothea), spec. n.Anapothea Miller, 1956 (Reduviidae), gen. n.Santainezia Miller, 1956 (Reduviidae), gen. n.bicolor Miller, 1956 (Santainezia), spec. n.